PERTUMBUHAN DAN PRODUKSI JARAK PAGAR (Jatropha curcas L.; Euphorbiaceae) PADA TIGA TINGKAT POPULASI TANAMAN DI LAHAN KERING BERPASIR - Sri Mulyaningsih; Djumali Djumali (BERITA BIOLOGI, 2015)
Seed production of Jatropha grown on dry land is very low. Productivity could be increased by increasing plant population size. This study aimed to obtain a plant population that was capable of supporting optimum growth and seed production on sandy upland. This research was conducted at the Asembagus Experimental Station, Situbondo, East Java from January to December 2012. The planting material used were seeds and cuttings. Three populations levels: (1) 2,500 plants ha-1 (2 m x 2 m), (2) 5,000 plants ha-1 (2 m x 1 m), and (3) 10,000 plants ha-1 (1 m x 1 m ) were arranged in a randomized block design with 5 replications. Destructive observations were made in each month to measure the dry weight of plants, shoot, root, leaf, and leaf area index.The production component were observed at harvesting time by measuring dry weight of fruit, fruit skin, seeds, 1000 fruits, and 1000 seeds. Data were analyzed by analysis of variance and LSD test of 5%. Results showed that the use of 10,000 plants ha-1 could increased dry weight of plants, shoots and roots by134.0-544.6%,125.9-549.4% and 167.8-693.3% respectively. They could also increased seed production by 77.5-178.2%.